2009
DOI: 10.3347/kjp.2009.47.4.409
|View full text |Cite
|
Sign up to set email alerts
|

Antigenemia and Specific IgM and IgG Antibody Responses in Rabbits Infected with Toxoplasma gondii

Abstract: Toxoplasmosis is usually diagnosed using serological tests with increases in specific IgG and IgM antibodies. However, these tests are not reliable in immunocompromised patients, nor is it possible to differentiate clearly between the acute and latent forms of toxoplasmosis [1,2]. Because a relatively high percentage of individuals have antibodies without a recognized parasite infection, the early detection of Toxoplasma gondii antigen in the serum or other body fluids of patients would help to diagnose correc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 11 publications
1
9
0
1
Order By: Relevance
“…Ig measurements in serum samples from dogs with different inflammatory diseases showed a 2.5‐fold significant increase in the IgM concentration in dogs with pyometra, whereas dogs with leishmaniasis showed a significant 5‐fold increase in IgG and IgM levels. IgM is considered an immunological marker for the early infectious phase where its levels increase relatively rapidly, while isotype switching, and increasing and persisting circulating levels of IgG are generally observed later . The results of the present study confirmed these immunologic principles, as significantly higher IgM, but not IgG, levels were detected in dogs with pyometra, an acute inflammatory disease, whereas in dogs with a chronic Leishmania spp.…”
Section: Resultssupporting
confidence: 84%
“…Ig measurements in serum samples from dogs with different inflammatory diseases showed a 2.5‐fold significant increase in the IgM concentration in dogs with pyometra, whereas dogs with leishmaniasis showed a significant 5‐fold increase in IgG and IgM levels. IgM is considered an immunological marker for the early infectious phase where its levels increase relatively rapidly, while isotype switching, and increasing and persisting circulating levels of IgG are generally observed later . The results of the present study confirmed these immunologic principles, as significantly higher IgM, but not IgG, levels were detected in dogs with pyometra, an acute inflammatory disease, whereas in dogs with a chronic Leishmania spp.…”
Section: Resultssupporting
confidence: 84%
“…The resultant analysis revealed a time-dependent significant increase in specific antibody levels following repeated antigenic exposure. The antibody responses wane down after withdrawal of antigenic exposure, possibly due to diminishing levels of circulating antigen ( Quan et al ., 2009 ). Although the magnitude of the antibody response noted was not very high and was limited only to post-antigen inoculation period, antigen-specific antibody production was observed in the study.…”
Section: Discussionmentioning
confidence: 99%
“…The protein concentrations of the lysates were measured using a protein assay kit (Bio-Rad, Richmond, VA, U.S.A.), and lysates were stored at −70°C. ELISA was performed using a previously reported method [ 12 ]. Plates were read at 490 nm using an automatic ELISA plate reader (Sunrise, Techan, Salzburg, Austria).…”
Section: Methodsmentioning
confidence: 99%